2021
DOI: 10.1111/1467-8551.12552
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Brand, Brand Origin and Brand User Stereotypes in Forming Value Perceptions

Abstract: Although the importance of various brand-related stereotypes held by consumers has been acknowledged in the marketing literature, their interplay has not yet been considered. We derive four alternative theoretical models of the relationships between brand, brand origin and brand user stereotypes and their effects on consumers' value perceptions. The four models are subsequently tested on two nationally representative samples in Germany and Serbia, respectively. The best-performing model in both studies predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 145 publications
(229 reference statements)
0
8
0
2
Order By: Relevance
“…Due to the context, time, or situation, individuals might infer higher warmth from highly competent professionals, lower competence from highly warm providers, etc. Hence, these two premises need to be considered when examining stereotypes in specific countries ( Diamantopoulos et al, 2021 ; Gidaković et al, 2022 ), industries, for vulnerable groups, and considering recent changes in current stereotypes (e.g., sexual identities, racial stereotypes, migrant circumstances such as refugees, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the context, time, or situation, individuals might infer higher warmth from highly competent professionals, lower competence from highly warm providers, etc. Hence, these two premises need to be considered when examining stereotypes in specific countries ( Diamantopoulos et al, 2021 ; Gidaković et al, 2022 ), industries, for vulnerable groups, and considering recent changes in current stereotypes (e.g., sexual identities, racial stereotypes, migrant circumstances such as refugees, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Recent scholars in marketing that have used the SCM have mentioned the need for further research in this field ( Leung et al, 2023 ; Pizzi et al, 2023 ; Ren et al, 2023 ). The authors indicated that, while the influence of the two main traits has been more widely studied in psychology, more research is needed to uncover how these traits influence consumers’ decision-making ( Kolbl et al, 2019 , 2020 ; Diamantopoulos et al, 2021 ; Gidaković et al, 2022 ) and behavior in the market ( Halkias and Diamantopoulos, 2020 ; Pizzi et al, 2023 ). Following this need for research, in the present study, we first take a closer look at prior findings in marketing and consumer behavior.…”
Section: Themes From Bibliographic Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering abstract cultural values embedded in corporate heritage brands (Balmer, 2011; Urde et al, 2007), we expect that shared cultural schema is not only associated with conceptual fluency but also relates to the perception of fit in the form of abstract traits and entities associated with the culturally charged brands and their extensions (Gidaković et al, 2022; Torelli et al, 2012). Because of the shared representations of stereotypical entities surrounding the culture‐product domain, we propose that the more salience and cultural congruity there are between the corporate heritage brand and the new extension category, the greater is the perception of fit.…”
Section: Research Hypothesesmentioning
confidence: 99%